Analisis Kualitas SDM dan Layanan Keagenan Perusahaan Pelayaran Nasional di Indonesia - Sugiyanto Sugiyanto (Institut Transportasi dan Logistik Trisakti, 2021)
This study aims to analyze the quality of domestic ship agency human resources at PT PELNI (Persero) Tanjung Priok Branch using descriptive methods and quantitative descriptive analysis techniques and reliable questionnaires. The results of the research data above, namely the variable X regarding the quality of human resources owned by PT PELNI (Persero) Tanjung Priok Branch as many as 53% answered doubt, while in the Y variable regarding Agency Services for ship agency customers, 30% answered. So it can be denied that the quality of human resources affects the agency services of domestic vessels at PT Pelni (Persero) Tanjung Priok Branch. The performance of the agency service quality of PT PELNI (Persero) Tanjung Priok Branch has decreased due to the lack of expertise possessed by the employees who serve it. So that to improve the quality of the agency owned by the company, it is necessary to pay attention to things such as: Training aimed at increasing knowledge, skills and attitudes, good communication coordination between colleagues, superiors, subordinates and customers, division of job duties, speed of agency services and accuracy of reporting and Network marketing enhancement.